1989
DOI: 10.1002/1520-6629(198904)17:2<119::aid-jcop2290170203>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Sense of community and political participation

Abstract: Current conceptualizations of sense of community suggest that this quality may be correlated with various forms of political participation. This notion was tested in the current study by measuring and computing relationships between sense of community and five different types of political participation: voting, campaigning, contacting political officials, working on public problems, and talking about politics. Indices of these political activities were further subdivided into those with local relevance and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 13 publications
3
63
0
2
Order By: Relevance
“…For example, in addition to Parker et al's (2001) findings, prior research has also demonstrated that sense of community is significantly related to personal well-being (Davidson & Cotter, 1991;Farrell, Aubry, & Coulombe, 2004), knowledge of and participation in substance abuse prevention activities (McGuire, 1997;Peterson & Reid, 2003), participation in voluntary associations Perkins et al, 1990), and political participation (Davidson & Cotter, 1989). Thus, sense of community has been found to be an important predictor of life satisfaction and many types of neighborhood-based problem solving efforts.…”
Section: Measuring Community Social Organizationmentioning
confidence: 88%
“…For example, in addition to Parker et al's (2001) findings, prior research has also demonstrated that sense of community is significantly related to personal well-being (Davidson & Cotter, 1991;Farrell, Aubry, & Coulombe, 2004), knowledge of and participation in substance abuse prevention activities (McGuire, 1997;Peterson & Reid, 2003), participation in voluntary associations Perkins et al, 1990), and political participation (Davidson & Cotter, 1989). Thus, sense of community has been found to be an important predictor of life satisfaction and many types of neighborhood-based problem solving efforts.…”
Section: Measuring Community Social Organizationmentioning
confidence: 88%
“…A sense of community also has been shown to have positive influence on various outcome variables, such as wellbeing (Davidson & Cotter, 1991;Obst & Tham, 2009), and participation Davidson & Cotter, 1989). These studies demonstrate that the notion of a sense of community is useful and helpful to understand not only the locational, but also the relational dimension of the setting and to the psychological dimension.…”
Section: Vygotsky's Understanding Of Culturementioning
confidence: 99%
“…Davidson and Cotter (1989) further used the scale to demonstrate a connection between PSOC and voting patterns. Davidson and Cotter (1997) condensed the scale into five items assuming unidimensionality and found internal consistencies for their three communities of .70, .64, and .66.…”
Section: Previous Research On Cohesion Dimensionsmentioning
confidence: 99%